2007
DOI: 10.1007/s11259-007-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polyether Ionophores on the Protective Immune Responses of Broiler Chickens against Angara Disease and Newcastle Disease Viruses

Abstract: Immunization against Angara disease virus (ADV), a serotype 4 avian adenovirus, and Newcastle disease virus (NDV), an avian paramyxovirus serotype 1, is the mainstay of a broiler vaccination programme, while polyether ionophores usually form an essential component of a broiler medication programme in most parts of India and Pakistan. The role of polyether ionophores in the protective immune responses of broiler chickens vaccinated and challenged with ADV and NDV was investigated. A total of 1600 birds were div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 61 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Also, anticoccidial drugs interfere with the development of immunity in chickens. Broadly speaking, ionophores in low concentration stimulate the immune response, and in higher doses have immunosuppressive effect [33, 42]. Long et al [28] found that monensin at 60–100 ppm reduced the immune response to infection with Eimeria , while concentration of 40 and 50 ppm allowed good development of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, anticoccidial drugs interfere with the development of immunity in chickens. Broadly speaking, ionophores in low concentration stimulate the immune response, and in higher doses have immunosuppressive effect [33, 42]. Long et al [28] found that monensin at 60–100 ppm reduced the immune response to infection with Eimeria , while concentration of 40 and 50 ppm allowed good development of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…These authors established that unlike cyclophosphamide, salinomycin (4), at a dosage of 0.1 g/kg, did not adversely affect the bursal, splenic, thymic and liver weight gain [ 106 ]. It was also established that NDV vaccinated chickens that received salinomycin (4) 60 mg/kg of feed had higher antibiotic titers at days 14, 21, 28, 35, 42 compared to unmedicated chickens [52,106] or vaccinated chickens that were medicated with monensin (2) 12 mg/kg instead [ 52 ]. These salinomycin medicated chickens also gained significantly more weight, p < 0.05, compared to all the other groups evaluated.…”
Section: 7mentioning
confidence: 92%
“…Several other carboxyl ionophores are also reported to have anticoccidial utility in chickens and turkeys. Although these are the most common additives used now, there are several other carboxyl ionophores reported to be more effective than additives marketed at present [49][50][51][52][53][54][55][56][57][58][59].…”
Section: 32mentioning
confidence: 99%
“…However, with ND vaccination regime, IFN-γ production in Con-A-stimulated splenocytes was significantly elevated in antibiotic-treated chickens compared with the non-medicated control group. These two studies (Munir et al, 2007;Khalifeh et al, 2009) support the view that antimicrobials can enhance cell-mediated immunity in broiler chickens.…”
Section: Effect Of Antimicrobials On Gut Microbiota Communitymentioning
confidence: 80%